Myopic governments and welfare-enhancing debt limits - Malte Rieth (European Central Bank (ECB), 2011)
This paper studies welfare consequences of a soft borrowing constraint on sovereign debt which is modeled as a proportional fine per unit of debt exceeding some reference value. Debt is the result of myopic fiscal policy where the government is assumed to have a smaller discount factor than the private sector. Due to the absence of lump-sum taxation, debt reduces welfare. The paper shows that the imposition of a soft borrowing constraint, which resembles features of the Stability and Growth Pact and which is taken into account by the policy maker when setting its instruments, prevents excessive borrowing. The constraint can be implemented such as to (i) control the long run level of debt, (ii) prevent debt accumulation, and (iii) induce debt consolidation. In all three cases the constraint enhances welfare and in a welfare ranking these gains outweigh the short run welfare losses of increasing the costs of using debt to smooth taxes over the business cycle.
Keywords: H3; H63; E6; 330; debt bias; fiscal constraints; Myopic governments; social welfare; Stability and Growth Pact